Workplace response of companies exposed to the 9/11 World Trade Center attack: a focus‐group study. Issue 1 (16th October 2012) - North, Carol S.; Pfefferbaum, Betty; Hong, Barry A.; Gordon, Mollie R.; Kim, You‐Seung; Lind, Lisa; Pollio, David E.
<x xml:space="preserve">Abstract</x> The terrorist attacks of 11 September 2001 (9/11) left workplaces in pressing need of a mental health response capability. Unaddressed emotional sequelae may be devastating to the productivity and economic stability of a company's workforce. In the second year after the attacks, 85 employees of five highly affected agencies participated in 12 focus groups to discuss workplace mental health issues. Managers felt ill prepared to manage the magnitude and the intensity of employees' emotional responses. Rapid return to work, provision of workplace mental health services, and peer support were viewed as contributory to emotional recovery. Formal mental health services provided were perceived as insufficient. Drawing on their post‐9/11 workplace experience, members of these groups identified practical measures that they found helpful in promoting healing outside of professional mental health services. These measures, consistent with many principles of psychological first aid, may be applied by workplace leaders who are not mental health professionals.